2016
DOI: 10.1051/matecconf/20164701001
|View full text |Cite
|
Sign up to set email alerts
|

Fresh State and Mechanical Properties of Self Compacting Concrete Incorporating High Volume Fly Ash

Abstract: Abstract. Self-compacting concrete is considered as a concrete which can be placed and compacted under its own weight without vibration. The elimination of the need for compaction leads to better quality concrete and substantial improvement of working conditions. This paper investigates the fresh state and mechanical properties of self-compacting concrete incorporating high volume fly ash. Fly Ash (FA) was mixed into self-compacting concrete (SCC) as a replacement for cement. Portland cement (PC) was partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…therefore, as indicated in Table 2, it has been proven that excessively substituting cement with y ash will gradually decrease the compression strength of SCC because pozzolanic material cause concrete to gain strength at a rate that is slower than cementitious materials. The similar in uence of high substitution of cement by y ash on SCC compressive strength is also additionally found in Mohamad et al (2015)'s study .According to the study's control mix compressive strength, after 60% cement substitution by y ash, the strength steadily decreased from more than 50.0 MPa to less than 30.0 MPa (Mohamad et al, 2015). A similar pattern of declining SCC compressive strength with a rising proportion of cement replacement by y ash has also been demonstrated by Dasarathy et al (2018).…”
Section: Using the Trial-and-error Methods In MIX Designssupporting
confidence: 71%
“…therefore, as indicated in Table 2, it has been proven that excessively substituting cement with y ash will gradually decrease the compression strength of SCC because pozzolanic material cause concrete to gain strength at a rate that is slower than cementitious materials. The similar in uence of high substitution of cement by y ash on SCC compressive strength is also additionally found in Mohamad et al (2015)'s study .According to the study's control mix compressive strength, after 60% cement substitution by y ash, the strength steadily decreased from more than 50.0 MPa to less than 30.0 MPa (Mohamad et al, 2015). A similar pattern of declining SCC compressive strength with a rising proportion of cement replacement by y ash has also been demonstrated by Dasarathy et al (2018).…”
Section: Using the Trial-and-error Methods In MIX Designssupporting
confidence: 71%
“…However, increasing the fly ash content up to 60% by wt. of cement lower the compressive strength at 7, 28 and 56 days [4]. In another study it was also found that the use of fly ash with percentage of 30% by wt.…”
Section: Introductionmentioning
confidence: 81%
“…It is found that 5% of fibers improved the tensile strength of composite in comparison with the pure HDPE. It is also found that the addition of fibers decreased the thermal stability of composites but increased its thermal crystallization temperature [10]. Replacement of 40% fly ash in the self-compacting concrete mixture had resulted with optimum workability, compressive strength and modulus of elasticity of the mixture with the highest compressive strength achieved was 27.2 MPa and MOE 31 GPa [11].…”
Section: Introductionmentioning
confidence: 92%